(untitled) (Research, Society and Development, 2020)
Introduction: Fear and anxiety in oral surgical procedures, unique to each individual, reduce the patient’s visits to the dental office and present themselves as a challenge for the dental surgeon in surgical dental practice. Objective: To understand, through a literature review, the factors that interfere with anxiety and fear in patients who have undergone minor oral surgery and implant treatment procedures. Material and Method: A bibliographic search was carried out in the PUBMED and SCIELO databases, selecting case control articles, epidemiological, prospective and with a maximum of 8 years in the literature. Results: The results showed that females have greater anxiety in procedures of minor oral surgery. Regarding the treatment with implants, there was no more anxious sex. Previous treatment experience is an important factor for the patient to be more predisposed to anxiety or fear. Conclusion: The anxiety of patients who undergo oral surgery procedures is still present in the outpatient context and its main causative factors are surgical complexity, the type of information received to understand the procedure, eating disorders, blood pressure, professional’s level of experience and the number of implants needed.